2009
DOI: 10.1093/nar/gkp059
|View full text |Cite
|
Sign up to set email alerts
|

The regulatory domain of the RIG-I family ATPase LGP2 senses double-stranded RNA

Abstract: RIG-I and MDA5 sense cytoplasmic viral RNA and set-off a signal transduction cascade, leading to antiviral innate immune response. The third RIG-I-like receptor, LGP2, differentially regulates RIG-I- and MDA5-dependent RNA sensing in an unknown manner. All three receptors possess a C-terminal regulatory domain (RD), which in the case of RIG-I senses the viral pattern 5′-triphosphate RNA and activates ATP-dependent signaling by RIG-I. Here we report the 2.6 Å crystal structure of LGP2 RD along with in vitro and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
144
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(157 citation statements)
references
References 48 publications
11
144
0
2
Order By: Relevance
“…Interestingly, each member of the RIG-I subfamily of DExD/H helicases senses viral RNA differently. For example, RIG-I senses 5′ triphosphate ds/ssRNA, MDA5 senses cytoplasmic dsRNA (33), and LGP2 senses dsRNA independent of 5′ triphosphates (34). In parallel, we found that two members of the RHA subfamily of DExD/H helicases sense microbial DNA differently: DHX36 senses CpG-A using the DEAH domain, whereas DHX9 senses CpG-B using the DUF domain.…”
Section: Discussionmentioning
confidence: 73%
“…Interestingly, each member of the RIG-I subfamily of DExD/H helicases senses viral RNA differently. For example, RIG-I senses 5′ triphosphate ds/ssRNA, MDA5 senses cytoplasmic dsRNA (33), and LGP2 senses dsRNA independent of 5′ triphosphates (34). In parallel, we found that two members of the RHA subfamily of DExD/H helicases sense microbial DNA differently: DHX36 senses CpG-A using the DEAH domain, whereas DHX9 senses CpG-B using the DUF domain.…”
Section: Discussionmentioning
confidence: 73%
“…Both MDA5 and LGP2 contain CTD, but the N-terminal CARDs are found only in MDA5. MDA5 senses viruses that are not detected by RIG-I via a distinct strategy, whereas LGP2 seems to function as a regulator of RIG-I and MDA5 activities through a currently unknown mechanism (29,30,(31)(32)(33)(34).In this study, we show that drh-1 and drh-3 of C. elegans are essential for antiviral RNAi but exhibit distinct antiviral activities. Using a transgenic approach developed to assay for the Significance Retinoic acid inducible gene I-like RNA helicases (RLHs) act as virus sensors in mammalian antiviral immunity.…”
mentioning
confidence: 62%
“…Both MDA5 and LGP2 contain CTD, but the N-terminal CARDs are found only in MDA5. MDA5 senses viruses that are not detected by RIG-I via a distinct strategy, whereas LGP2 seems to function as a regulator of RIG-I and MDA5 activities through a currently unknown mechanism (29,30,(31)(32)(33)(34).…”
mentioning
confidence: 99%
“…Importantly, the inhibitory effect was unique to LGP2, as inclusion of FLAG‐tagged MDA5 or FLAG‐tagged RIG‐I had little effect on dicing efficiency (Figs 4C and EV3C). In contrast to full‐length LGP2, purified LGP2 CTD only modestly decreased in vitro dicing of dsRNA despite its ability to associate with Dicer and to bind dsRNA with high affinity (Li et al , 2009; Pippig et al , 2009; Figs 4D and EV3D). Furthermore, there was little difference between the LGP2 CTD and a CTD K634E mutant, which completely lacks RNA binding.…”
Section: Resultsmentioning
confidence: 99%